2022
DOI: 10.1098/rsos.220299
|View full text |Cite
|
Sign up to set email alerts
|

Individual risk-taking behaviour in black-capped chickadees (Poecile atricapillus) does not predict annual survival

Abstract: Within species, individuals often show repeatable differences in behaviours, called ‘animal personality’. One behaviour that has been widely studied is how quickly an individual resumes feeding after a disturbance, referred to as boldness or risk-taking. Depending on the mechanism(s) shaping risk-taking behaviour, risk-taking could be positively, negatively, or not associated with differences in overall survival. We studied risk-taking and survival in a population of free-living black-capped chickadees ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Calling in this latter case would therefore likely be riskier, resulting in an increased time of silence following the acoustic predation cue. These results support previous studies [77][78][79] that found if a predator stimulus is visual as opposed to acoustic, then foraging rates in those prey species are reduced and anti-predatory behavior (vigilance, calling) is increased. Interestingly, with the exception of chickadee calling latency being predicted by conspecific number, our results are not mirrored between the studies.…”
Section: Plos Onesupporting
confidence: 91%
“…Calling in this latter case would therefore likely be riskier, resulting in an increased time of silence following the acoustic predation cue. These results support previous studies [77][78][79] that found if a predator stimulus is visual as opposed to acoustic, then foraging rates in those prey species are reduced and anti-predatory behavior (vigilance, calling) is increased. Interestingly, with the exception of chickadee calling latency being predicted by conspecific number, our results are not mirrored between the studies.…”
Section: Plos Onesupporting
confidence: 91%
“…[ 75 ] Poecile atricapillus black-capped chickadee Aves Michelangeli et al . [ 76 ] Tiliqua rugosa sleepy lizard Reptilia Mitchell and Biro [ 25 ] Danio rerio zebrafish Actinopterygii Mitchell et al . [ 77 ] Poecilia reticulata Trinidadian guppy Actinopterygii Mitchell et al .…”
Section: Methodsmentioning
confidence: 99%
“…Each feeder was located in a grassy area, approximately 5 m from the nearest forest edge. The Arboretum feeder was placed within the GVSU VanSteeland Arboretum while the AuSable feeder was approximately 12 m from a little-used exit door of GVSU's AuSable Hall (Figure S1 in the online supplemental materials); the locations were selected to be as similar as possible while still remaining close enough ( 130 m apart) so that the same birds would visit both (Mathot et al, 2022). Both sites experienced minimal human disturbance during our trials.…”
Section: Foraging Trialsmentioning
confidence: 99%